2004
DOI: 10.1021/ja0473788
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Photochemistry of a Pyrene Dihydrodioxin (PDHD) and Its Radical Cation:  A Photoactivated Masking Group for ortho-Quinones

Abstract: Pyrene dihydrodioxins (1 and 2) have been synthesized and shown to be effective photochemical blocking groups for pyrene-4,5-dione (3). The mechanism of quinone release proceeds through the formation of a remarkably stable radical cation. Direct evidence is provided that this radical cation is not only thermally labile but also photochemically labile, and that both pathways lead to quinone extrusion. Once initiated with UV light, the pyrene quinone product serves as an electron-transfer photosensitizer for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Previous work with the 1,1-di-4-methoxyphenylDHD in the nanosecond regime, indicated that upon excitation the pyrene moiety readily lost an electron to form a pyrene radical cation with a very conspicuous intense absorption at 453 nmand that this species survived into the microsecond time domain [11]. In the present work, we have extended these observations into the picosecond and femtosecond time domains.…”
Section: Pyrene Radical Cation As An Intermediate In Pyrene Quinone Rsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous work with the 1,1-di-4-methoxyphenylDHD in the nanosecond regime, indicated that upon excitation the pyrene moiety readily lost an electron to form a pyrene radical cation with a very conspicuous intense absorption at 453 nmand that this species survived into the microsecond time domain [11]. In the present work, we have extended these observations into the picosecond and femtosecond time domains.…”
Section: Pyrene Radical Cation As An Intermediate In Pyrene Quinone Rsupporting
confidence: 58%
“…This reaction is reversed by irradiation with shorter wavelength (short wavelength visible or UV light) that reforms the original ortho-quinone and olefin [11]. In previous studies, this quinone releasing property of dihydrodioxins has been investigated as a possible tool for DNA cleavage [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the ESI mass spectrum, [ M +H] + was observed at m / z 459. In the UV/Vis spectrum, the absorption band at λ max =448 nm (n–π* transition in 2 ) disappeared after the reaction 9. Instead, charge transfer (CT) between 1 a and 4 is clearly observed around 500 nm, owing to the increased donor ability of the aromatic moiety (see http://www.wiley-vch.de/contents/jc_2002/2008/z705139_s.pdf in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…In the ESI mass spectrum, [ M +H] + was observed at m / z 459. In the UV/Vis spectrum, the absorption band at λ max =448 nm (n–π* transition in 2 ) disappeared after the reaction 9. Instead, charge transfer (CT) between 1 a and 4 is clearly observed around 500 nm, owing to the increased donor ability of the aromatic moiety (see http://www.wiley-vch.de/contents/jc_2001/2008/z705139_s.pdf in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%